Early Detection of Speech Delay through Education for Cadres and Mothers of Toddlers - Huvaid, Sevilla Ukhtil; Yulianita; Mindayani, Sri (JURNAL PENGMAS KESTRA (JPK), 2024)
Speech delay is often found in children. Parents often do not understand the condition of their child experiencing speech delay and the efforts that must be made to handle it. Leaving a child without treatment can have more severe impacts. Manual detection by health workers and the role of parents that can be done through integrated health posts, also cannot be done in detail and continuously. Based on a qualitative field survey conducted on cadres and mothers of toddlers in the Batubusuk area, it was found that cadres and mothers of toddlers did not know exactly about speech delay. The results of the counseling activities showed that there was an increase in the knowledge of mothers of toddlers before and after counseling about speech delay, while there was no change in the cadres. Educational activities need to be improved through various methods and media, efforts that can be made include early detection when integrated health posts are carried out through speech screening in toddlers and monitoring the development of toddler speech through scheduled door-to-door services.